Analysis of Adaptation of Students Studying under the Flipped Classroom Model to the Conditions of Distance Learning - G. R. Chaynikova (Открытое образование (Москва))
Purpose of study. In the situation of the coronavirus pandemic, distance learning technologies have become the only way to organize the educational process. The transition to distance learning required both adaptation of the content, tools and methods of teaching to the new conditions, and adaptation on the part of students, in particular, it demanded from them to be much more independent and responsible, as well as the ability to effectively use their time. In this connection, the aim of the study was to analyze how the technology of blended learning allows students to better adapt to the conditions of distance learning.Materials and methods. The author considered the following as the main indicators of students’ adaptation to distance learning: 1) actual results of learning activities; 2) the degree of students’ satisfaction with the results of their learning activity; 3) self-assessment of readiness to use ICT tools in learning process, development of independent work and self-organization skills, self-report on the psychological state. The analysis of pedagogical literature on blended learning made it possible to identify a number of important principles which the learning process should be based on in the flipped classroom model, the analysis of which, in turn, showed that they fully correspond with the principles of distance learning. All this suggests that blended learning as a component of full-time instruction, implemented from the first term when teaching English as an academic discipline, should help students better adapt to the conditions of distance learning. To confirm this hypothesis, an analysis and comparison of the results of learning activities in the conditions of blended and distance learning, as well as a questionnaire of students were conducted.Results. Comparison of the current and final performance in English as an academic subject in the conditions of blended and distance learning did not reveal any significant changes. Survey analysis showed that the transition to distance learning was a challenge for most students and demanded from them to make significant efforts  to adapt, which was manifested in a decreased level of satisfaction with the results of their learning activities in general, an increased level of anxiety, as well as highlighting a number of difficulties that they had to face. However, a comparison of data obtained on the discipline “English language”, where training was initially built on the flipped classroom model, and data on distance learning in general allows the author to conclude that the technology of blended learning makes it possible to reduce a number of difficulties, in particular, technical difficulties when switching to distance learning, and the indicator of satisfaction with the results of their learning activities shows that the flipped classroom model allows students to more fully realize their abilities and achieve the desired results not only in the conditions of blended learning, but also when switching to distance one.Conclusion. The analysis made it possible to show a significant potential of blended learning in the conditions of introducing information technologies in education. At the same time, it is necessary to keep in mind the importance of pedagogical support in the context of e-learning.